Micro, small, medium enterprises (MSMEs) in Tacloban City how sustainable are they? - Antido, Zyra Mae B.; Corot, Rossnel O.; Jopio, Marie Chell D.; Ramucala, Ross Ali M.; Solajes, Shannen G. (2016)
This research studied the MSMEs operating in Tacloban City for 10 years or more in contracting and providing services, manufacturing and financial institutions industry. Findings showed that most of the businesses in these industries have survived because of their monetary investments. However, they still face several problems in their operations, marketing, human resource and financial aspect of their businesses. Thu, it is recommended that the manager or the proprietor of each businesses should be knowledgeable in enterprise management, marketing strategy such as diversification and innovation, financial management and human resource empowerment.